Sarah, plain & tall [videorecording (DVD)] : Winter's end - Jordan, Glenn, 1936-; MacLachlan, Patricia; Close, Glenn, 1947-; Walken, Christopher, 1943-; Hearn, George; Randall, Lexi; Bell, Christopher; Osment, Emily (Hallmark Entertainment, 2002)
A mysterious stranger appears at the Kansas farm of Jacob and Sarah Witting. The stranger is Jacob's father, John, who abandoned him and his mother when he was a child. Although John establishes relationships with Sarah and his grandchildren, he struggles to reconcile with his son. Third part of a trilogy.